Value prospect and technical characteristics of 6G - Xiaomin NIU (Dianxin kexue)
Combined with the value identification for 5G,the prospect of 6G values was made,and the characteristics of coverage,openness,security and independence of 6G were analyzed.It concludes that if 6G is viewed as the fundamentals for developing both the technological innovation and business mode innovation and is put into the top priority satisfying the expectations for experiencing applications and contents of 6G,the 6G may be far better than 5G,not just 1G advantage,numerically.